Spousal Violence Against Women in India: A Social–Ecological Analysis Using Data From the National Family Health Survey 2015 to 2016 - Ahmad, Jaleel (Journal of interpersonal violence, 2021)
Even after enactment of the Protection of Women From Domestic Violence Act 2005, over the last 10 years, the rate of decline of prevalence of spousal violence against women has remained low in India. This study attempts to explain the experience of spousal violence using a social–ecological framework. We analyzed the National Family Health Survey 2015 to 2016 (NFHS-4) data of 66,013 ever-married women aged 15 to 49 years. Participants in the domestic violence module of the NFHS-4 reported their experience of violence committed by their husband within the 12 months preceding the survey. Multilevel logistic regression analyses were done to determine the association between spousal violence and different explanatory variables of various levels of social ecology including variables on women’s empowerment. About one fourth of ever-married women reported experiencing any form of violence during the last year. The experience of spousal violence was significantly associated with social ecology at multiple levels. At the individual level, the odds of experiencing physical violence were higher among younger women, who married at a younger age, had an age gap of 3 to 4 years with her husband, and had more children. Women in vulnerable groups, with poor economic status, and members of marginalized communities had higher odds of experiencing spousal violence. Women had high odds of experiencing spousal violence if living in a social ecology with unfavorable social norms, higher rates of domestic crimes, and a higher prevalence of underage marriage. The association of spousal violence with women’s empowerment remained inconclusive. The results argue for manipulating contextual factors to empower women to challenge gender-related equations and investing in education for gender sensitization at the higher level social ecologies.